A Study on the Employment Support Service System for Visually Impaired College Students in China - Bo, Zhou; Hock, Kway Eng (South Asian Journal of Social Sciences and Humanities, 2024)
At present, the problem of difficult employment for disabled college students in China is becoming more and more prominent, and the construction of an employment support service system for colleges and universities is one of the most important means of alleviating the employment pressure on disabled college students and promoting the healthy development of society. Based on the perspectives of visually impaired college students and colleges and universities, this study adopts qualitative research methods such as interview method and observation method, selects 10 visually impaired students from a college in China as the research object, and statistically analyses the raw data of the interviews with NVivo data analysis tools, and builds a college employment support service system with the core of education and training and support, employment guidance and consulting, social resources integration and enhancing social and enterprise inclusiveness. The service system is of great practical significance for promoting high-quality employment and better integration of visually impaired students into society, as well as creating a harmonious and inclusive employment support environment.